2015
DOI: 10.2754/avb201584010019
|View full text |Cite
|
Sign up to set email alerts
|

Choanal and cloacal aerobic bacterial flora in captive green iguanas: a comparative analysis

Abstract: The aims of this study were to characterize the choanal and cloacal aerobic bacterial flora in healthy captive green iguanas and to compare it with the bacterial flora of the biofilm present in the water container of each terrarium. Samples were collected from the choana and the cloaca of 20 healthy captive adult green iguanas and from the biofilm of 15 water containers. The final identification of aerobic bacteria was performed by matrix-assisted laser desorption ionization time-of-flight mass spectrometry. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Iguana species can carry in their intestines Salmonella species (17,18) and Escherichia coli (19)(20)(21). The prevalence of E. coli in iguana species ranges from 40 to 70%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iguana species can carry in their intestines Salmonella species (17,18) and Escherichia coli (19)(20)(21). The prevalence of E. coli in iguana species ranges from 40 to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Ricord's iguana (Cyclura ricordi) the prevalence reported was 50% (22), while in the land iguana (Conolophus pallidus) from the Galapagos Island it was 70.83% (19). Regarding the green iguana, studies have reported an E. coli prevalence of 40% (21) and 53.2% (18). To the best of our knowledge, whether the green iguana can carry DEC pathotypes has not been previously investigated and it was the main motivation for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many species of snakes are raised as pet animals, and good knowledge of their physiological and behavioral needs allows for proper management in captivity, where the goal is to create a domestic habitat similar to that of their origin (Stahl, 2002; Mitchell, 2004). The specific environmental conditions of the terrarium, such as temperature, humidity, aeration, moisture and organic substances, are favorable growth factors for commensal microorganisms and opportunistic pathogens (Ebani & Fratini, 2005; Romero et al, 2015). Snakes could become spreaders of potentially pathogenic bacteria, which can represent a serious threat to themselves and humans (Goldstein et al, 1981; Ebani & Fratini, 2005; Romero et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Iguana species can carry in their intestines Salmonella species (16, 17) and Escherichia coli (18–20). The prevalence of E. coli in iguana species ranges from 40 to 70 %.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Ricord’s iguana ( Cyclura ricordi ) the prevalence reported was 50% (21), while in the land iguana ( Conolophus pallidus ) from the Galapagos Island it was 70.83 % (18). Regarding the green iguana, studies have reported an E. coli prevalence of 40 % (20) and 53.2 % (17). To the best of our knowledge, whether the green iguana can carry DEC pathotypes has not been previously investigated and it was the main motivation for this study.…”
Section: Introductionmentioning
confidence: 99%